Extensively drug-resistant tuberculosis in the UK: 1995 to 2007. Issue 6 (23rd March 2009) - Abubakar, I; Moore, J; Drobniewski, F; Kruijshaar, M; Brown, T; Yates, M; Anderson, C; Smith, E G; Magee, J; Lipman, M; McMenamin, J; Ruddy, M; et al.
Abstract : Background: The emergence of multidrug-resistant tuberculosis (MDRTB) and extensively drug-resistant tuberculosis (XDRTB) is a threat to global tuberculosis control. Limited information is, however, available on the outcome of XDRTB cases. This study describes the susceptibility to second- and third-line antituberculosis drugs among MDRTB cases and treatment outcome of identified XDRTB cases. Method: The results of second-line antituberculosis drug susceptibility tests in the UK between January 1995 and December 2007 were retrospectively reviewed and clinicians contacted for treatment outcome of XDRTB cases. Participants included all 678 patients with culture-confirmed MDRTB in the UK. The main outcome measures were the proportion of isolates resistant to second-line antituberculosis drugs and treatment outcome for XDRTB cases. Results: Among MDRTB isolates, levels of resistance to amikacin, capreomycin, ciprofloxacin, cycloserine, ethionamide and p -aminosalicylic acid (PAS) were 5.5, 3.4, 5.6, 5.1, 14.0 and 16.7%, respectively. Six XDRTB cases (0.9% of MDR cases) were identified during this period. Two further cases of XDRTB were reported in 2008. Five individuals with XDRTB died of tuberculosis within 3 years of diagnosis and three are still on treatment. Conclusion: Levels of MDRTB remain low, and those of XDRTB very low, in this high income country. The case fatality ratio among XDRTB cases was high despite low levels of HIV co-infection.